Research on the Construction of Practical Teaching Mechanism of Applied Undergraduate Tourism Management Major and the Starting Time of the Mechanism: Take Zhaoqing University as an Example - Chen, Haiming; Chen, Fang (International Journal of Social Sciences and Public Administration, 2024)
This paper addresses the existing issues in the practical teaching of tourism management majors, establishing four mechanisms for applied undergraduate tourism management practical education, namely, the expansion training social practice mechanism, the innovation and entrepreneurship ability cultivation mechanism under the big creation project platform, the professional competition skill practical teaching mechanism, and the "exploratory internship" mechanism under the social practice platform. According to different stages in the academic system, corresponding practical teaching mechanisms are arranged: in the freshman year, an open practice mechanism is initiated to deepen students' understanding of theoretical knowledge; in the sophomore and junior years, a multi-scenario practice mechanism is implemented to enhance students' practical abilities and innovation and entrepreneurship capabilities; in the senior year, a comprehensive internship and exploratory practice mechanism is launched to thoroughly train students' professional skills and innovative thinking. The aim is to achieve progressive and integrated practical ability cultivation throughout the entire academic journey, providing strong support for training high-quality applied tourism management talents that meet market demands.